El Libro de Séneca contra la yra e saña y su relación con BnF ms. Latin 6390 - Juan Héctor Fuentes (Atalaya)
One of the most relevant problems when it comes to editing medieval translations and adaptations is the reconstruction of the underlying text. Regarding the Libro contra la ira e saña, the detailed study of the marginal annotations to the latin text of the De ira preserved in BnF ms. lat. 6390 evidences the close relationship between the comments and the Spanish romanceamiento with respect to the structure of the work and the adaptation to the forma tractatus.